Metal-Free N-Arylation of Indolines with Diaryliodonium Salts - Riedmüller, Stefan; Nachtsheim, Boris J. (Synlett, 2015)
The N-arylation of indolines using diaryliodonium salts as electrophilic arylating reagents is described. Without the use of any additional additives, the desired N-aryl indolines could be obtained in up to 85% yield.
Keywords: amination; hypervalent iodine; metal-free; arylation; indoline